ANALISIS KEBUTUHAN PENGEMBANGAN MEDIA PEMBELAJARAN PRAGMATIK BEBASIS AI TERHADAP MATERI TINDAK TUTUR MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA, UNIVERSITAS NEGERI PADANG - Putri Apika Sari; Tressyalina (EDU RESEARCH, 2024)
This study aims to 1) analyze the need for the use of AI-based pragmatic learning media in teaching speech act material in higher education; 2) obtain insights and challenges faced by lecturers and students in using conventional learning media for speech act material; and 3) design and develop AI-based learning media that can enhance students' understanding of speech act material. The subjects of this study are lecturers and students from the Indonesian Language and Literature Education Study Program (PBSI) at the Faculty of Languages and Arts, Universitas Negeri Padang. Data collection techniques were carried out through in-depth interviews, classroom observations, and document analysis. The data analysis technique used is descriptive qualitative analysis. The findings indicate that 1) The current use of conventional learning media is considered less effective in delivering complex speech act material, which requires a deep understanding of social context; 2) The challenges faced by lecturers include the limited availability of media that can depict the dynamics of speech acts in a real and contextually relevant manner; 3) Students face difficulties in understanding speech act material through traditional learning media and desire more interactive and contextual media; 4) The AI-based learning media developed is an interactive application that simulates various speech act contexts and provides automatic feedback, which is expected to enhance students' understanding of the material.